Effects of binary (Lithium/Natrium)2 carbonates on the phase and microstructural stability of Lscf-Sdc for low temperature solid oxide fuel cells - Hamimah Abd. Rahman,; Linda Agun,; Ng, Kei Hoa; Sufizar Ahmad,; Nur Azmah Nordin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Most studies focus on introducing of doped ceria carbonate into cathode materials to enhance the cathode ionic conductivity for low temperature solid oxide fuel cell. In this work, we aim to identify the influence of Lithium/Natrium binaries (Li/Na)2 carbonates addition on Lanthanum Strontium Carbonate Ferrite-Samarium-Doped Ceria (LSCF-SDC) composite cathode on the phase and microstructural stability under long-term durability of 1000 h. Three different binaries (Li/Na)2 carbonate of 67:33, 62:38, and 53:47 mol.% were incorporated into LSCF-SDC via high energy ball milling method. The phase and microstructural stability as a function of operating temperature (400 and 600 °C) were studied using X-ray diffraction (XRD) and field emission scanning electron microscope (FESEM). Archimedes principle was applied to evaluate the porosity of the cathode pellets. Electrochemical impedance spectroscopy measurements were performed by using impedance setup at 600 °C under open-circuit condition. The XRD findings demonstrated that cathodes able to retain their chemical phases after stability test. Qualitative results show that the cathode morphology exhibits a slight increment on the particle size after the ageing process at 1000 h. All cathodes prepared at various binary carbonate ratio still maintain their porosity values between 26 and 32% after long-term stability test. This finding has yielded a smaller area specific resistance of 0.66 Ω.cm2 at 600 °C. Therefore, incorporating binary (Li/ Na)2 carbonate in LSCF-SDC shows a good combination when insignificant changes observed after long-term stability test of 1000 h.